Climate Sustainability Lives Related to The Rate of Development in The Tembalang Education Area - Imaniar Putri Nastiti (Eduvest - Journal of Universal Studies, 2024)
The Higher Education Area in Tembalang District has increased significantly since Diponegoro University made a Campus on Jalan Prof. Soedarto, SH as the main campus. In the first 10 (ten) years, the ability of indigenous people to survive against migrants and changes in activities has gone through many stages. A quick observation of the face of the identified area has a positive effect, namely revitalization. However, the alignments and policies of the Government and Higher Education Institutions towards Indigenous Peoples began to be needed when the migration rate of the Indigenous People was very high. This study aims to look at the sustainability of the climate of living, especially by the indigenous people of Tembalang District, and if it is associated with the high level of development in the area. The method of obtaining data and information used in this research is to conduct field observations and interviews with key persons.